Synthesis of new tacrine analogues from 4-amino-1H-pyrrole-3-carbonitrile - Salaheldin, Abdellatif M. (2010)
An easy preparation of 4-aminopyrrole-3-carbonitrile derivatives, and their transformation into new substituted pyrrolo[3,2-b]pyridines is described, in one step, via Friedländer reaction under microwave irradiation and classical heating methods. The use of microwave irradiation led to high conversion and shorter times.